The impact of commissioning for rhinosinusitis in England. (December 2015) - Soni‐Jaiswal, A.; Philpott, C.; Hopkins, C.
Abstract : Objectives: To assess the compliance of clinical commissioning groups (CCGs) in England with the ENT‐UK rhinosinusitis commissioning guide produced in collaboration with the Royal College of Surgeons England and the National Institute of Clinical Excellence. We also aimed to assess the ease of accessibility of data from CCGs. Design: Audit of compliance of English CCGs with the ENT‐UK rhinosinusitis commissioning guide. Setting: CCGs in England Participants: A total of 58 of the 221 CCGs in England were included and chosen because they were the first CCGs authorised by NHS England, or alternately, the CCGs forecasted to have a deficit in their first year of operation. Their websites were reviewed; when information was not easily accessible, a freedom of information request was submitted to the relevant CCG. Main outcome measures: Compliance with commissioning guidelines for rhinosinusitis. Results: Thirteen percent of CCGs had restrictive referral criteria in place, largely unrelated to published evidence‐based guidance. The routine use of multiple courses of oral steroids, prescription of antibiotics, CT scanning within primary care, and delaying referral for a year, prior to referral to a specialist were recommended against published advice. Conclusions: Restricting access to surgery may contribute to poorer outcomes and a decrease in the patient's quality of life. This is against the NHS constitution and is open to legal challenge. We encourage all ENT surgeons to review policies of their local CCG and engage with commissioners to ensure that their patients have evidence‐based care.